Customer repurchase decision for the same brand of laptop product using binary logistic regression - Mangkuto, Shidiq Umar; Saputra, Tubagus Chandra; Fadhilah, Savira Maghfiratul; Heikal, Jerry (International Journal of Applied Finance and Business Studies, 2025)
The laptop industry faces significant challenges and opportunities amidst a dynamic and competitive market. Understanding the factors that influence consumers' repurchase decisions is crucial for laptop manufacturers and marketers to develop effective strategies. This research aims to analyze the factors that influence the decision to repurchase laptop products using the Binary Logistic Regression method. This research uses primary data from 271 respondents in Indonesia which was collected via an online questionnaire. Data analysis was carried out using Binary Logistic Regression. The dependent variable is the laptop repurchase decision (yes/no). Independent variables include age, gender, domicile, income, expenses, laptop price, and place of purchase. The analysis shows that income and place of purchase have a significant effect on the decision to repurchase a laptop. The prediction model has an overall accuracy of 62%, with an accuracy of 56.3% for predictions of not making a repeat purchase and 67.6% for predictions of making a repeat purchase. Other factors such as age, gender, domicile, expenditure and laptop price did not show a significant influence. The value proposition is based on the results of this research, namely segmenting the market based on income level and adjusting product needs for each segment so that each product released can be right on target.